2019
DOI: 10.1111/sji.12800
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lymphatic malformations using primary cells and tissue transcriptomes

Abstract: Lymphatic malformations (LMs) are disfiguring congenital anomalies characterized by aberrant growth of lymphatic vessels. They are broadly categorized histopathologically as macrocystic and microcystic. Although sclerotherapy has shown some success in the treatment of macrocystic malformations, there has been less progress with developing treatment strategies for microcystic malformations. In this study, we characterized lymphatic endothelial cells isolated from lymphatic and lymphaticovenous malformations. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…5,25 Most OLM cases become clinically evident until the age of two, but small and asymptomatic lesions may receive a later diagnosis. 3,5,6,12,14,21,22,27,39,43,44 Data from the multicenter study and the case report studies corroborate these findings, since children and adolescents presented larger OLMs than did adults or elderly individuals. This may also be the reason for such different mean ages among case series studies.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…5,25 Most OLM cases become clinically evident until the age of two, but small and asymptomatic lesions may receive a later diagnosis. 3,5,6,12,14,21,22,27,39,43,44 Data from the multicenter study and the case report studies corroborate these findings, since children and adolescents presented larger OLMs than did adults or elderly individuals. This may also be the reason for such different mean ages among case series studies.…”
Section: Discussionmentioning
confidence: 66%
“…21,38 The literature has stated that LM has no sex or racial predilection. 3,5,6,15,39 Regarding OLM, two studies based on biopsy files had observed a female predilection, but both were conducted with a small sample. 31,40 By contrast, data from the present multicenter study and the literature review showed the absence of predilection for any sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report identified that the genes encoding FOXF1 and DIRAS3 are highly overexpressed in LM-LECs ( 70 ). Haploinsufficiency of FOXF1and FOXC2 may be associated with macrocystic LM ( 71 ).…”
Section: Molecular Pathogenesismentioning
confidence: 99%